2022
DOI: 10.1038/s42003-022-03596-2
|View full text |Cite
|
Sign up to set email alerts
|

Activated-memory T cells influence naïve T cell fate: a noncytotoxic function of human CD8 T cells

Abstract: T cells are endowed with the capacity to sense their environment including other T cells around them. They do so to set their numbers and activation thresholds. This form of regulation has been well-studied within a given T cell population – i.e., within the naïve or memory pool; however, less is known about the cross-talk between T cell subsets. Here, we tested whether memory T cells interact with and influence surrounding naïve T cells. We report that human naïve CD8 T cells (TN) undergo phenotypic and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The contribution of this cluster to overall T cell suppression phenotype is further demonstrated through comparison of T cell suppressor signature scores between patients with arthritis and no irAEs ( Figure 5 E). Like other central memory populations, the genes in this cluster were associated with IL-3 and IL-5 secretion 24 and class I signaling 25 ( Figure 5 F).…”
Section: Resultsmentioning
confidence: 78%
“…The contribution of this cluster to overall T cell suppression phenotype is further demonstrated through comparison of T cell suppressor signature scores between patients with arthritis and no irAEs ( Figure 5 E). Like other central memory populations, the genes in this cluster were associated with IL-3 and IL-5 secretion 24 and class I signaling 25 ( Figure 5 F).…”
Section: Resultsmentioning
confidence: 78%
“…Memory cells have a lower activation threshold than naive T cells [36] , [37] and rapidly acquire an effector state upon re-encounter with the antigen presented even at much lower doses [37] , [38] , [39] . It was also shown that memory T cells are relatively independent of co-stimulation from antigen-presenting cells (APCs) [20] , [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recently our lab showed that activated memory CD8 T cells acquire a novel non-cytotoxic function by which they can interact and influence the phenotype and transcriptome of naïve CD8 T cells. In this scenario, they acquire two states (1) an activated/memory T cell state and (2) a unique hybrid state between naïve and effector/activated memory cells ( 123 ) ( Figure 4C ). Since both cell populations were sorted from the same healthy subject, we speculate that activated memory T cells are presenting self-antigen to naïve T cells generating auto-reactive T cells.…”
Section: Cytotoxic and Non-cytotoxic Functions Of Cd8 T Cellsmentioning
confidence: 99%